2018
DOI: 10.1002/ajmg.a.38639
|View full text |Cite
|
Sign up to set email alerts
|

A homozygous TTN gene variant associated with lethal congenital contracture syndrome

Abstract: Pathogenic variants in the TTN gene have been reported to cause various cardiomyopathies and a range of skeletal muscle diseases, collectively known as titinopathies. We evaluated a consanguineous family multiple members affected with a lethal congenital contracture syndrome. Using exome sequencing, we identified a homozygous c.36122delC (p. P12041Lfs*20) variant in exon 167 in the fetal IC isoform of TTN. The finding expands the phenotypes that can be caused by pathogenic variants TTN, which should be conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 11 publications
(13 reference statements)
1
22
0
Order By: Relevance
“…Junctional reads bridging exons 181 and 170 are detected in adult skeletal muscle (Savarese et al, ), inferring the novel frameshift variants found in families A and F affect transcripts expressed in skeletal muscle. Of note, exons 213‐217 are not expressed at significant levels in cardiac tissue (Savarese et al, ) and reported individuals with a metatranscript‐only pathogenic TTN variant did not present with a cardiac phenotype (herein and in Chervinsky et al, ; Fernández‐Marmiesse et al, ; Oates et al, ).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Junctional reads bridging exons 181 and 170 are detected in adult skeletal muscle (Savarese et al, ), inferring the novel frameshift variants found in families A and F affect transcripts expressed in skeletal muscle. Of note, exons 213‐217 are not expressed at significant levels in cardiac tissue (Savarese et al, ) and reported individuals with a metatranscript‐only pathogenic TTN variant did not present with a cardiac phenotype (herein and in Chervinsky et al, ; Fernández‐Marmiesse et al, ; Oates et al, ).…”
Section: Introductionmentioning
confidence: 91%
“…Genetic diagnosis of a recessive congenital titinopathy was further complicated for Families A and F whose second TTN frameshift variants involved metatranscript‐only exons (exons 181 and 170, respectively). In support of pathogenicity, there are several recent reports of autosomal recessive congenital titinopathies associated with variants within metatranscript‐only exons 163, 172, 181, 201 (Oates et al, ), 197 (Fernández‐Marmiesse et al, ), and 167 (Chervinsky et al, ). Junctional reads bridging exons 181 and 170 are detected in adult skeletal muscle (Savarese et al, ), inferring the novel frameshift variants found in families A and F affect transcripts expressed in skeletal muscle.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Once AMC is identified and an approximate clinical diagnosis allows for the assignment to an etiological subgroup, genetic testing can help distinguish among an expanding number of conditions, depending on test availability. However, genome‐wide sequencing studies in the last years have shed light on a seemingly endless list of diseases or disease phenotypes, and an exploding number of genes and molecular pathways, that can be associated with contractures (Abiusi et al, ; Aggarwal, Das Bhowmik, Tandon, & Dalal, ; Beecroft et al, ; Chai et al, ; Chervinsky et al, ; Filges et al, ; Hall & Kiefer, ; Hunter et al, ; Nguyen et al, ; Stevenson, Vincent, Spellicy, Friez, & Chaubey, ). For the time being, genetic testing, however, will be complicated by the limited time during pregnancy for molecular studies, and its added value will therefore also largely depend on the dating of the pathological ultrasound finding.…”
Section: Prenatal Cytogenomics and Molecular Genetics And Genomic Tesmentioning
confidence: 99%
“… 5 , 6 Recessive TTN mutations cause a wide range of muscle disease with or without cardiomyopathy which have been reported under different terms in the past, such as recessive early‐onset myopathy with fatal cardiomyopathy, centronuclear myopathy (CNM), core myopathy with heart disease, and arthrogryposis multiplex congenita with myopathy and others. 3 , 7 , 8 , 9 , 10 , 11 , 12 …”
Section: Introductionmentioning
confidence: 99%